Apoptosis in Cancer Cells Is Induced by Alternative Splicing of hnRNPA2/B1 Through Splicing of Bcl-x, a Mechanism that Can Be Stimulated by an Extract of the South African Medicinal Plant, Cotyledon orbiculata - Makhafola, Tshepiso Jan; Mbele, Mzwandile; Yacqub-Usman, Kiren; Hendren, Amy; Haigh, Daisy Belle; Blackley, Zoe; Meyer, Mervin; Mongan, Nigel Patrick; Bates, David Owen; Dlamini, Zodwa (Frontiers in Oncology, 2020)
Background: Alternative splicing is deregulated in cancer and alternatively spliced products can be linked to cancer hallmarks. Hypothesis: Targeting alternative splicing could offer novel effective cancer treatments. Study design and methods: We investigated the effects of the crude extract of a South African medicinal plant, Cotyledon orbiculata, on cell survival of colon (HCT116) and esophageal (OE33 and KYSE70) cancer cell lines. Using RNASeq, we discovered that the extract interfered with mRNA regulatory pathways. Results: The extract caused hnRNPA2B1 to splice from the hnRNPB1to the hnRNPA2 isoform, resulting in a switch in the BCL2L1 gene from Bcl-xL to Bcl-xS causing activation of caspase-3-cleavage and apoptosis. Similar splicing effects were induced by the known anti-cancer splicing modulator pladienolide B. Knockdown of hnRNPB1 using siRNA resulted in decreased cell viability and increased caspase-3-cleavage, and over-expression of hnRNPB1 prevented the effect of C. orbiculata extract on apoptosis and cell survival. The effect of the hnRNPA2/B1 splicing switch by the C. orbiculata extract increased hnRNPA2B1 binding to Bcl-xl/s, BCL2, MDM2, cMYC, CD44, CDK6 and cJUN mRNA. These findings suggest that apoptosis in HCT116, OE33 and KYSE cancer cells is controlled by switched splicing of hnRNPA2B1 and BCL2L1, providing evidence that hnRNPB1 regulates apoptosis. Inhibiting this splicing could have therapeutic potential for colon and esophageal cancers. Conclusion: Targeting hnRNPA2B1 splicing in colon cancer regulates splicing of BCL2L1 to induce apoptosis. This approach could be a useful therapeutic strategy to induce apoptosis, and restrain cancer cell proliferation and tumor progression. Here, we found that the extract of Cotyledon orbiculata, a South African medicinal plant, had an anti-proliferative effect in cancer cells, mediated by apoptosis induced by alternative splicing of hnRNPA2B1 and BCL2L1.